Fate of moderate secondary mitral regurgitation in patients undergoing aortic valve replacement for severe aortic regurgitation. Issue 9 (7th June 2022) - Del Forno, Benedetto; Ascione, Guido; Gramegna, Federica; Carino, Davide; Lapenna, Elisabetta; Verzini, Alessandro; Alfieri, Ottavio; Castiglioni, Alessandro; Maisano, Francesco; De Bonis, Michele
Abstract: Objectives: Moderate secondary mitral regurgitation is common in patients with severe aortic regurgitation, but whether it has to be addressed at the time of aortic valve surgery remains unclear. With this study, we evaluated the long‐term fate of moderate secondary mitral regurgitation in this specific scenario. Methods: Between January 2004 and January 2018, in 154 patients admitted to our institution for treatment of severe aortic regurgitation, a moderate secondary mitral regurgitation was diagnosed. Ninety‐four patients underwent isolated aortic valve replacement (group 1) and 60 patients underwent also concomitant mitral valve annuloplasty (group 2). Results: One death (1.1%) occurred in group 1, whereas two deaths (3.3%) occurred in group 2 ( p = .561). At 11 years, the cumulative incidence function of cardiac death, with noncardiac death as a competing risk was 11.5 ± 5.11% in group 1 and 8.3 ± 5.15% in group 2 ( p = .731). The cumulative incidence function of mitral valve reintervention, with death as a competing risk, was 3.7 ± 2.61% in group 1 and 4.5 ± 4.35% in group 2 ( p = .620) at 11 years. Secondary mitral regurgitation improved to ≤mild in 66% and 76% of the survivors of group 1 and group 2, respectively ( p = .67). Conclusions: In our experience, in patients with moderate secondary mitral regurgitation undergoing aortic valve replacement for severe aortic regurgitation, concomitant mitral valve annuloplasty did not improve the long‐term survival, the incidence of cardiac death and mitral valve reoperation or the evolution of the mitral valve disease.